On variants of n-sensitivity in semiflows. Issue 8 (3rd August 2022) - Thakur, Rahul; Das, Ruchi
Abstract : We introduce various types of n -sensitivity, such as multi- n -sensitivity, strong n -sensitivity, syndetic n -sensitivity, thick n -sensitivity and thickly syndetic n -sensitivity in general semiflows, and provide several sufficient conditions under which a semiflow possesses such notions. We prove that multi- n -sensitivity, thick n -sensitivity and thickly syndetic n -sensitivity are all equivalent for an almost open P - M -semiflow whose acting semigroup is discrete and abelian. We also discuss the relationships among these notions, and provide examples wherever implications are not true.